PlayScrum - a card game to learn the Scrum agile method - Fernandes, João M. (2010)
To motivate and engage students and, consequently, improve the quality of learning, some researchers suggest new ways of teaching, including the use of serious games in the classroom. This paper describes PlayScrum, a new card game devised to allow university-level students to learn Scrum, an agile software development method. We present the card game, its rules, and how it supports the main concepts of the Scrum method. We also discuss how PlayScrum was validated, based on questionnaires filled in by master students who have played it.